The Process of Investigation on Child Criminal Theft Committed Under Diversion - Wahyu Ismail; Jawade Hafidz; Denny Suwondo (Law Development Journal, 2022)
The purpose of this research is to find out and analyze the process of investigating the crime of children committing theft which is not diverted. To find out and analyze the obstacles in the process of investigating the crime of children committing theft that is not diverted and the solution. The method used by the researcher isnormative legal approachandThe specifications in this study are descriptive.The sources and types of data in this study are secondary data obtained from library studies. Data analyzed qualitatively. Based on the results of the study thatThe Process of Investigating the Crime of Children Committing Theft That Wasn't Done Diversioni.e. investigators make summons, arrests, search bodies/houses, confiscate evidence, detain and file cases they handle. In addition, investigations of children who commit crimes of theft are carried out in a family atmosphere to children who carry out the investigation process. consideration or advice from community counselors or if necessary to educational experts, psychologists, psychiatrists, religious leaders, social workers and other experts in Cirebon Regency.The obstacle isThere is no Social Welfare Organization (LPKS), not all cases can be diverted and detention for investigation purposes too short. The solution is the Police Coordinates with the Government on LPKS, Investigators Provide Advice to Perpetrators and Victims, Police Conduct Workshops to Discuss the Juvenile Justice System Act.